EKSPLORASI PROSES KONSTRUKSI LITERASI FINANSIAL SISWA SD MELALUI PEMBELAJARAN MATEMATIKA REALISTIK (PMR) DALAM KONTEKS KEUANGAN SEHARI-HARI. - Roikhan Syahrul Ramadhani; Ichda Wahyuni, Holy; Naila, Ishmatun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of literacy understanding among elementary school students remains a serious problem. This is due to a lack of contextual mathematics learning and a failure to connect number concepts to students’ everyday financial experiences. This condition makes it difficult for students to apply basic mathematical concepts in money management, such as saving, comparing prices, and planning expenses. This study aims to explore the process of financial literacy construction in students through the application of PMR (Realistic Mathematics Learning) utilizing everyday financial contexts as teaching resources and emphasizing mathematical activities based on real-world experiences. This research employed a qualitative descriptive approach with a case study design, where data sources consisted of school teachers and students involved in everyday financial learning. Data collection techniques included classroom observations, in-depth interviews, and documentation of student activities. The collected data were analyzed using the Miles and Huberman interactive model, comprising data reduction, data presentation, and conclusion drawing. The results of this study indicated that PMR facilitates the construction of students’ financial literacy, reflected in three dimensions: (1) knowledge through mathematical modeling and financial record-keeping skills; (2) skills through the application of arithmetic operations and opportunity cost analysis in budget planning; and (3) attitudes through the development of key financial priorities and savings awareness. This construction was developed through mathematical modeling, interactive group discussions, and the transformation of concrete experiences into formal representations. Social interaction and teacher scaffolding were crucial factors in developing understanding, attitudes, and simple financial decision-making skills.